Preparation, Conduct, and Experimental Results of the AVR Loss-of-Coolant Accident Simulation Test - Krüger, K.; Bergerfurth, A.; Burger, S.; Pohl, P.; Wimmers, M.; Cleveland, J. C. (Nuclear science and engineering, 1991)
A loss-of-coolant accident (LOCA) is one of the most severe accidents for a nuclear power plant. To demonstrate inherent safety characteristics incorporated into small high-temperature gas-cooled reactor (HTGR) designs, LOCA simulation tests have been conducted at the Arbeitsgemein-schaft Versuchsreaktor (AVR), the German pebble-bed high-temperature reactor plant. The AVR is the only nuclear power plant ever to have been intentionally subjected to LOCA conditions without emergency cooling. The planning and licensing activities including pretest predictions performed for the LOCA test are described, and the conduct of the test and experimental results are presented. The LOCA test was planned to create conditions that would exist if a rapid LOCA occurred with the reactor operating at full power. The test demonstrated this reactor's safe response to an accident in which the coolant escapes from the reactor core and no emergency system is available to provide coolant flow to the core. The test is of special interest because it demonstrates the inherent safety features incorporated into optimized modular HTGR designs. The main LOCA test lasted for 5 days. After the test began, core temperatures increased for ∼13 h and then gradually and continually decreased as the rate of heat dissipation from the core exceeded the simulated decay power. Throughout the test, temperatures remained below limiting values for the core and other reactor components.